Clinical assessment and morphological changes of minor salivary glands in patients with secondary Sjogren’s Syndrome - Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat; Kashmoola, Muhannad Ali (2018)
Aim: To study the labial salivary gland biopsy fi ndings and to assess the clinical condition of the patients with secondary Sjogren’s syndrome patients. Material and methods: Fifty-six patients were involved in this study,full history was taken and complete clinical examination was done for the period of 15 months duration. Schirmer’s tear test, salivary fl ow rate were done for all patients. Labial salivary gland biopsy was performed and sent for histopathological study. Results: Schirmer’s tear test was positive with signifi cant reduction in the tear fl ow (P ≤ 0.01), in all patients . A signifi cant reduction in the salivary fl ow rate (p<0.01) in all patients .Clinical assessment showed parotid gland enlargement in 8 patients. Intraoral examination revealed a candidal infection in four patients. The histopathologic study for labial salivary gland biopsy showed a chronic infl ammatory process with lymphocytic infi ltration, acinar atrophy and proliferation of the ductal epithelium which obliterate the duct lumen. Conclusion: Patients with secondary Sjogren’s syndrome proved by labial salivary gland biopsy had a signifi cantly greater frequency to parotid gland enlargement and susceptibility to fungal infection.